Improved water resistance of TA-modified soy adhesive: Effect of complexation. (July 2021) - Zhu, Xiangwei; Song, Changyuan; Sun, Xiuzhi; Wang, Donghai; Cai, Dongna; Wang, Zhike; Chen, Yizhou; Chen, Xi
Abstract: The poor water resistance of protein adhesives seriously restricted their practical applications. Though many crosslinking agents, i.e. phenol formaldehyde, epoxy resins etc., can enhance the wet adhesion, high-proportion use of synthetic additives reduce intrinsic sustainability of protein formulations, and thus green yet robust protein adhesives are still highly expected. Herein, tannic acid (TA), a woody bio-extract abundant in catecholic hydroxyls, was used to improve the wet adhesion of soy protein (SP) adhesive. For further improved water resistance, the supramolecular architecture of SP-TA was tuned by different stabilizers, including zinc oxide nanoparticle (ZnO), ferric chloride (FeCl3 ) and glutaraldehyde (GH), aiming to enhance the intermolecular hydrogen bonding (H-bond), coordination or covalent bonding respectively. Results indicate that the ZnO-induced H-bond could simultaneously strengthen SP-TA interaction while retain the catechol reactivity of TA to the substrate, thus demonstrating the best water resistance. The optimized dry and wet adhesion strength reached 2.02 and 1.40 MPa respectively, which even exceeded the values of commercially available adhesives. Advantageously, these findings provide a rational perspective to modulate the adhesion/cohesion balance of protein-TA complex and pave the way toward facile processing of high-performance soy adhesive. Graphical abstract: Image 1 Highlights: A high-performance wet adhesive was developed by tuning complexation between soy protein (SP) and tannic acid (TA). Stabilization effects by zinc oxide nanoparticle (ZnO), ferric chloride or glutaraldehyde were compared. Adhesives modified by ZnO manifested the best catechol functionality and water resistance. The optimized wet adhesion strength reached 1.40 MPa, a value superior to commercial adhesives.